PROSES LAYANAN PEKERJAAN SOSIAL OLEH SATUAN BAKTI PEKERJA SOSIAL (SAKTI PEKSOS) BERSERTIFIKAT DI DKI JAKARTA - Ifan, Maykel (Istek Widuri Jakarta, 2020)
The quality of social work services is important in alleviating social problems. The quality is evidenced by the existence of a social worker certificate issued by a professional certification board. This is to ensure that the competence of both knowledge and skills possessed can not be done by just anyone. So this study explores the process of social work services performed by certified social workers based on social work values, knowledge and skills. This research with qualitative approach, involving 5 certified social worker informants in DKI Jakarta through interview, observation and documentation study. The result of research shows that social work process conducted by the five informants clearly shows that the value, knowledge, and skills of social work are applied in social work service process which includes initial approach, assessment, preparation of intervention plan, implementation of intervention, monitoring, evaluation and termination. Through this social work service process, the five informants can solve the social problems of the beneficiaries of social work services.